Spatial social interaction: An explanatory framework of urban space vitality and its preliminary verification. (February 2022) - Guo, Xiangmin; Yang, Yanwen; Cheng, Ziyuan; Wu, Qi; Li, Chenjing; Lo, Tiantian; Chen, Fukai
Abstract: Urban space is vital to contemporary urban life. However, the digital era has had an enduring impact on global urban space. The vitality of many physical urban spaces has been declining, with many of their functions replaced by online activities. It has become crucial to theoretically reconsider the key elements of the attractiveness of urban space and to find an effective practical measurement to improve urban space vitality. Therefore, this paper applies an interdisciplinary view of sociology and urban planning, raising an explanatory framework to show that the major determinant of urban space vitality has shifted to "spatial social interaction", which is derived from people's social needs. Based on this assumption, this paper further presents various factors of spatial social interaction and constructs a quantitative model. In addition, it verifies the model through an empirical analysis of OCT Loft in Shenzhen, China. In the process, the interaction parameters of typical spaces are calculated and compared with the actual situation and shows a positive correlation. The construction of the theoretical framework and preliminary verification are expected to provide insights into the worldwide revitalization of urban space and to help in the preevaluation of related designs. Highlights: Propose the essential connotation of spatial interaction. Establish a theoretical framework of spatial vitality based on social interaction. Verifies the spatial interaction quantitative model through an empirical analysis on OCT Loft.